2011
DOI: 10.1111/j.1365-2788.2011.01454.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of conditioning impairments in children with Down syndrome, autistic spectrum disorders and mental age-matched controls

Abstract: These findings are discussed in terms of there implications for reward-based educational intervention programmes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 29 publications
1
7
0
Order By: Relevance
“…However, neural activity was only significantly correlated to behavioral performance during reversal. Our data also show that a neurodevelopmental example of an interneuron deficit leads to difficulty navigating a reversal task (15,17,26) in agreement with reports from human patients with schizophrenia and impaired cognition (4548). In the Plaur mice, these behavioral deficits likely reflect decreased numbers of fast-spiking PV + interneurons, which led to altered encoding of decisions (correct vs error), elevated baseline OFC activity, diminished differences between baseline firing and trial epochs, a reduction in predicted outcome encoding, and a lack of correlation between OFC firing and behavior.…”
Section: Discussionsupporting
confidence: 91%
“…However, neural activity was only significantly correlated to behavioral performance during reversal. Our data also show that a neurodevelopmental example of an interneuron deficit leads to difficulty navigating a reversal task (15,17,26) in agreement with reports from human patients with schizophrenia and impaired cognition (4548). In the Plaur mice, these behavioral deficits likely reflect decreased numbers of fast-spiking PV + interneurons, which led to altered encoding of decisions (correct vs error), elevated baseline OFC activity, diminished differences between baseline firing and trial epochs, a reduction in predicted outcome encoding, and a lack of correlation between OFC firing and behavior.…”
Section: Discussionsupporting
confidence: 91%
“…Despite aspects of learning theory being used to a degree in educational strategies in autistic children, there has been surprisingly little clinical investigation on the nature of reward-based learning in ASD. One study reported that ASD patients performed as well as their mental age-matched controls in an instrumental conditioning task (Reed, Staytom, Stott, & Truzoli, 2011), suggesting a discrepancy with the data obtained from the NRXN1␣ KO animal model. However, studies that directly assess instrumental learning in patients are rare and this topic certainly requires further exploration, both clinically and preclinically, before conclusions on the translational validity of this aspect of the model can be determined.…”
Section: Discussionmentioning
confidence: 97%
“…Certain aspects of learning are identified as strengths. Children with DS perform favorably in paradigms of observational learning (observing the actions of others) [Reed et al, ] and when associating objects with rewards [Kogan et al, ]; whereas, they have greater difficulty with instrumental learning (manipulating the environment to meet their needs) [Wishart, ; Ohr and Fagen, ; Reed et al, ]. Their higher social motivation and responsiveness to positive reinforcement likely make socially oriented learning more successful.…”
Section: Cognitive Functioningmentioning
confidence: 99%